How-to-Do-It Stories Rank High with Editors in South Carolina - Anne Bellissimo (Journal of Applied Communications, 1979)
All of the 19 daily (AMs and PMs) and the more than 100 weekly newspaper editors in South Carolina were sent questionnaires.